Investigating the effect of a school-based WASH intervention on soil-transmitted helminth and schistosome infections and nutritional status of school children in Ethiopia: a quasi-experimental study - Gemechu Tadesse; Yonas Wuletaw; Kalkidan Mekete; Heven Sime; Elodie Yard; Laura Appleby; Jack Grimes; Nigussie Dejene; Iain Gardiner; Adama Kazienga; Souheila Abbeddou; Michael French; et al. (Parasites & Vectors, 2024)
Abstract Background The impact of access to improved water, sanitation and hygiene (WASH) and health education on large-scale deworming programs aimed at controlling soil-transmitted helminth (STH) and schistosome (SCH) infections has not been well studied. We assessed the additional impact of improved WASH infrastructure and health education at schools on STH and SCH infections in Ethiopia. Methods The study used a quasi-experimental design under which 30 schools were assigned to either an intervention (15 schools) or control (15 schools) arm. Both arms received a standard deworming treatment and lunch. In the intervention arm, improved WASH and health education were provided. At three consecutive time points (baseline in 2013, 2014 and 2015), the prevalence and intensity of STH and SCH infections and the nutritional status [hemoglobin concentrations and physical growth (height and weight)] were determined. To verify whether interventions were successfully implemented, the WASH status at school and the student knowledge, attitudes and practices related to WASH (WASH-KAP) were recorded. Differences in metrics between arms at baseline (2013) and follow-up (2015) were assessed both within and between the arms. Results A significant increase in scores for both the school WASH and student KAP was found in the intervention arm, indicating successful implementation of the intervention. The prevalence of any STH infection was significantly reduced in the intervention arm but not in the control arm (F = 4.486, p = 0.034). There was a significantly greater reduction in the intensity of infection of hookworm and Ascaris lumbricoides compared to baseline in both arms. The intervention did not affect school children’s height-for-age z-score (intervention arm * time coef = 0.12, p = 0.400) and body mass index-for-age z-scores (intervention * time coef = − 0.06, p = 0.526). Hemoglobin concentrations increased significantly more in the control than the intervention arm (coef = − 0.16, p = 0.006). Conclusions Although the intervention did increase school WASH and student WASH-KAP, our study found poor evidence of the additional benefit of improved WASH and health education to deworming and school food programs on parasite re-infection and the health outcomes of children. Graphical Abstract